EDUCATION FOR PEACE AND HUMAN RIGHTS: CONTRIBUTIONS TO SPECIES MANAGEMENT IN A TIDE-DOMINATED TROPICAL ESTUARY (Interdisciplinary Studies Journal, 2026)
The Brazilian wrasse (Ucides cordatus) is ecologically and economically important on the Brazilian coast, acting as a keystone species, aiding in nutrient cycling and bioturbation in mangroves, and serving as a subsistence resource for communities and traditional peoples. The study of long-term population dynamics aimed to contribute to the sustainable management of the species, as well as environmental monitoring. Life tables were constructed based on the carapace width of monitored individuals, resulting in survival rates and curves, as well as demography by life stage. The Lefkovich matrix was developed from these results and allowed the calculation of the population growth rate. The populations in the Piraquê-Açu (PA) and Piraquê-Mirim (PM) rivers exhibit distinct dynamics, reflecting different degrees of resilience and vulnerability, and follow a type I survival pattern, with higher mortality in adult stages and slow population growth. The analysis revealed that the PM has higher juvenile mortality, while the PA shows better survival in this phase, which may be a determining factor for its greater stability. Thus, population management strategies have been proposed to contribute to the sustainable coexistence of the species with the ecosystem and the sustenance of human populations that depend on this resource.
Keywords: Ucides cordatus; population dynamics; Management; Conservation